1997
DOI: 10.1590/s0100-879x1997000300008
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of glucose and prolactin on GLUT2 expression in cultured neonatal rat islets

Abstract: We studied the synergistic effect of glucose and prolactin (PRL) on insulin secretion and GLUT2 expression in cultured neonatal rat islets. After 7 days in culture, basal insulin secretion (2.8 mM glucose) was similar in control and PRL-treated islets (1.84 ± 0.06% and 2.08 ± 0.07% of the islet insulin content, respectively). At 5.6 and 22 mM glucose, insulin secretion was significantly higher in PRL-treated than in control islets, achieving 1.38 ± 0.15% and 3.09 ± 0.21% of the islet insulin content in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In agreement with previous reports (Boschero et al 1988, Crepaldi-Alves et al 1997, culture of neonatal rat islets induces significant increase in insulin release into the culture medium. Islets cultured for 3 days (0.46 ± 0.06 (n ¼ 17 wells; 8-10 islets per well) ng insulin/islet/h; P < 0.05) or 7 days (1.030 ± 0.17 (n ¼ 16 wells; 8-10 islets per well) ng insulin/islet/h; P < 0.001) showed an approximately 2-fold and 3-fold increase in insulin release compared to 24 h-cultured islets (0.26 ± 0.02 (n ¼ 17 wells; 8-10 islets per well) ng insulin/islet/h).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous reports (Boschero et al 1988, Crepaldi-Alves et al 1997, culture of neonatal rat islets induces significant increase in insulin release into the culture medium. Islets cultured for 3 days (0.46 ± 0.06 (n ¼ 17 wells; 8-10 islets per well) ng insulin/islet/h; P < 0.05) or 7 days (1.030 ± 0.17 (n ¼ 16 wells; 8-10 islets per well) ng insulin/islet/h; P < 0.001) showed an approximately 2-fold and 3-fold increase in insulin release compared to 24 h-cultured islets (0.26 ± 0.02 (n ¼ 17 wells; 8-10 islets per well) ng insulin/islet/h).…”
Section: Resultssupporting
confidence: 93%
“…accordance with our work, numerous studies have shown that fetal and neonatal islets, when cultured for a certain period of time, display an increased insulin response to suprastimulatory concentrations of glucose as well as to other secretagogues (Shimizu et al 1983, Dudek et al 1984, Freinkel et al 1984, Masaki et al 1987, Boschero et al 1993, Yderstraede & Flindt-Egebak 1995, Collares-Buzato et al 2001. Such process of in vitro maturation is even enhanced by exposure to prolactin (Boschero et al 1993, Crepaldi-Alves et al 1997, CollaresBuzato et al 2001. It has been suggested that the gradual increase in insulin secretory capacity of islets and fetal pancreata in vitro can not only be explained by islet hyperplasia but involves the maturation of critical steps of stimulus-secretion coupling process in the B-cell (Dudek et al 1984, Freinkel et al 1984, Boschero et al 1993, Yderstraede & Flindt-Egebak 1995, CrepaldiAlves et al 1997.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In neonatal rat islets PRL treatment enhances islet insulin content and early insulin secretion (5456), also increasing islet sensitivity to glucose (53). This effect may be partly explained by the increased β-cell and liver glucose transporter GLUT2 in membrane as seen in cultured neonatal rat islets (57, 58). In transgenic female mice with hyperprolactinemia, hyperandrogenism, and hyperprogesteronemia induced by overexpression of the human chorionic gonadotropin β-subunit, a 1-week treatment with cabergoline has been found to significantly reduce body weight and to improve dyslipidemia and insulin resistance up to complete normalization of triglycerides and insulin, besides PRL levels (61).…”
Section: Effects On Glucose Abnormalitiesmentioning
confidence: 99%